The Shift in Divorce Patterns among Muslim Families in Gorontalo - Dikson T. Yasin (Faculty of Law, Universitas Pekalongan, 2025)
In Gorontalo, over 600 divorce rulings were issued in 2022, with the majority stemming from a weakening of marital commitment. This study investigates the evolving divorce patterns among Muslim families in Gorontalo, highlighting two key shifts. First are attitudinal shifts, where social media platforms are frequently misused as instruments of online infidelity. Second are behavioral shifts, where marriage is increasingly perceived as a temporary and negotiable bond, no longer anchored firmly in religious and moral values. Employing a qualitative, field-based approach, this research draws upon direct observations and in-depth interviews with divorced or divorcing Muslim couples. An empirical framework is used to explore the socio-cultural and technological dynamics shaping divorce, with a particular emphasis on judicial data from the Gorontalo Religious Court. Findings reveal a substantial transformation in the patterns of divorce driven by two interrelated forces. First, the pervasive presence of social media has accelerated the internalization of materialistic and consumerist ideals, which in turn erode moral consciousness and reshape both attitudes and behaviors within the marital relationship. Second, social media has contributed to a transformation in divorce typology—from traditionally talaq-based divorces (initiated by husbands) to a rise in contested divorces (initiated by wives). This shift reflects changing power dynamics and an emerging trend in which women increasingly claim their legal agency to terminate marriages they perceive as dissatisfying or unjust